+0  
 
0
32
1
avatar+1372 

Help.

 
NotSoSmart  Jan 11, 2018
Sort: 

1+0 Answers

 #1
avatar+80779 
+2

3x^2 - 4 =  -x^4         add x^4 to both sides

 

x^4 + 3x^2  - 4  = 0     factor as

 

(x^2 + 4) (x^2 - 1)  = 0

 

(x^2 + 4)  (x + 1)  ( x-1)  = 0

 

Setting the last two factors to 0 and solving for x produces   x = -1 and x  = 1

 

Settting the first factor to 0, we have

 

x^2 +4  = 0   subtract 4 from both sides

 

x^2  =   -4         take both roots

 

x = ±√-4    =  ±2i

 

So the solutions are    1, -1, 2i, 2i

 

 

(s + 4v)^5  =

 

s^5  +  5(s^4)(4v) + 10(s^3)(4v)^2  + 10(s^2)(4v)^3  + 5(s)(4v)^4  + (4v)^5  

 

s^5  +  20s^4v  + 160s^3v^2   + 640s^2v^3  + 1280sv^4  +  1024v^5  [third answer ]

 

 

cool cool cool

 
CPhill  Jan 11, 2018

3 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details